2018
DOI: 10.1126/scisignal.aau7987
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian pigmentation is regulated by a distinct cAMP-dependent mechanism that controls melanosome pH

Abstract: The production of melanin increases skin pigmentation and reduces the risk of skin cancer. Melanin production depends on the pH of melanosomes, which are more acidic in lighter-skinned than in darker-skinned people. We showed that inhibition of soluble adenylyl cyclase (sAC) controlled pigmentation by increasing the pH of melanosomes both in cells and in vivo. Distinct from the canonical melanocortin 1 receptor (MC1R)–dependent cAMP pathway that controls pigmentation by altering gene expression, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 92 publications
4
37
0
Order By: Relevance
“…Neutral pH preserves TYR and TYRPs functions, while acidic pH suppresses TYR function without altering its expression (discussed in later section). Zhou et al reported that the soluble adenylyl cyclase (sAC)-dependent pathway negatively modulates melanin production by decreasing the pH of melanosomes [19].…”
Section: Melanin and Melanogenesismentioning
confidence: 99%
“…Neutral pH preserves TYR and TYRPs functions, while acidic pH suppresses TYR function without altering its expression (discussed in later section). Zhou et al reported that the soluble adenylyl cyclase (sAC)-dependent pathway negatively modulates melanin production by decreasing the pH of melanosomes [19].…”
Section: Melanin and Melanogenesismentioning
confidence: 99%
“…However, less well understood is the role of sAC-dependent cAMP signaling in pigmentation. Recent evidence suggests that sAC regulates pigmentation by altering the pH of melanosomes (Ota, Zhou, & Zippin, 2017;Zhou et al, 2018). Tyrosinase, the rate-limiting enzyme of melanin synthesis, is highly sensitive to pH (Ancans et al, 2001;Ito, Suzuki, Takebayashi, Commo, & Wakamatsu, 2013); thus, alteration in melanosome pH is predicted to affect tyrosinase activity.…”
Section: Amp S I G Naling In Pi G Mentati On By B Eni G N Mel Anomentioning
confidence: 99%
“…In fact, the pH of melanosomes is reported to be higher in darker‐skinned individuals compared to lighter‐skinned individuals, and this difference in pH is thought to contribute to the variations in skin and hair color (Fuller, Spaulding, & Smith, 2001; Schallreuter, Kothari, Chavan, & Spencer, 2008). Zhou et al demonstrated that inhibition of sAC enhances eumelanin synthesis by increasing melanosomal pH and tyrosinase activity (2018). sAC‐dependent alteration of melanosomal pH occurred rather quickly, suggesting that melanosomal pH is dynamically regulated (Zhou et al., 2018).…”
Section: Camp Signaling In Pigmentation By Benign Melanocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the pH of the human skin surface plays a crucial importance as a clinical criterion in terms of biochemical and medical studies, controlling the barrier function of skin to prevent microbial (or bacterial) colonization (e.g., by Staphylococcus aureus and Malassezia ) ( 21 ). For inappropriate pH levels induced by exposure to dusts or sunlight, excessive hormones, or wearing protective gear, certain pH-dependent enzymes (β-glucocerebrosidase and acidic sphingomyelinase) are unable to function to form a protective membrane on human skin, often leading to the occurrence of severe skin diseases in the human body, such as inflammatory skin diseases (e.g., irritant contact dermatitis, atopic dermatitis, or acne) ( 22 ), infections (e.g., fungal infections or candidal intertrigo) ( 23 ), or skin carcinoma ( 24 ). For accurate in situ diagnosis and personalized treatment of skin diseases, facile and direct collection of biofluids is critically needed, along with reusable and instantaneous quantification of pH levels ( 17 ).…”
Section: Introductionmentioning
confidence: 99%